2017
DOI: 10.1509/jmr.14.0625
|View full text |Cite
|
Sign up to set email alerts
|

What Happens Online Stays Online? Segment-Specific Online and Offline Effects of Banner Advertisements

Abstract: Many firms are allocating increasing parts of their advertising budgets to banner advertising. Yet, for firms that predominantly sell offline, existing research provides little guidance on online advertising decisions. In this study, the authors analyze the impact of banner advertising on consumers’ online and offline behavior across multiple distinct campaigns for one focal firm, which predominantly sells through the offline channel. Results suggest that banner and TV advertising increase website visit incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Reports from industry sources have shown that consumers respond better to integrated marketing campaigns (e.g., a 73% boost over standard email campaigns; Safko 2010). In academia meanwhile, the majority of research considering online promotions and advertisements has typically focused on how consumers respond to these strategies through online only measures (e.g., Manchanda et al 2006), though this has begun to change in recent years with more research examining offline consequences to omnichannel strategies (Lobschat et al 2017;Kumar et al 2017).…”
Section: Online/offline Integration and Complete Convergencementioning
confidence: 99%
“…Reports from industry sources have shown that consumers respond better to integrated marketing campaigns (e.g., a 73% boost over standard email campaigns; Safko 2010). In academia meanwhile, the majority of research considering online promotions and advertisements has typically focused on how consumers respond to these strategies through online only measures (e.g., Manchanda et al 2006), though this has begun to change in recent years with more research examining offline consequences to omnichannel strategies (Lobschat et al 2017;Kumar et al 2017).…”
Section: Online/offline Integration and Complete Convergencementioning
confidence: 99%
“…This appears to help drive website traffic, which in turn creates positive sales outcomes. Moreover, it is important for marketers to encourage website visits, as research indicates that these visits can improve offline sales as well [45].…”
Section: Discussion and Future Research Suggestionsmentioning
confidence: 99%
“…Parry et al [12] found that alcohol intake is third most momentous infections and social violence, accounting for 40% of violence, 15% of malfunctions and 15% of traffic accidents within South Africa [9]. These have the impact of advertising alcoholic beverages and promoting on the behaviour of individuals, particularly youth, with completely different views reckoning on the angle and subject of their explicit interests [13]. Still, within the field of study, Sunyani Technical University (STU), no study is available on the effect of advertising on alcoholic beverages on the buying or consuming behaviour of adolescents with only a few pounds currently available in Ghanaian literature.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…Alcohol consumption is a widespread activity and varies according to culture, distance and time depending on consumption habits [13]. The moment people start drinking alcohol is often determined by their respective companies.…”
Section: Prevalence Of Alcohol Consumptionmentioning
confidence: 99%